Penerapan Efektivitas Modul Pembelajaran Berbasis Proyek Pada Mata Kuliah Teknologi Pengolahan Buah Dan Sayur - Tri Rizki; Surhaini (Yayasan Rahmatan Fiddunya Wal Akhirah, 2025)
Project-Based Learning (PBL) is regarded as a successful strategy in higher education for improving students' comprehension and practical skills, particularly in application- based courses. The purpose of this study is to evaluate how well the project-based learning approach raises student interest and proficiency in a technology course on fruit and vegetable processing. 66 students enrolled in the course served as the sample for the One Group Pretest-Posttest research design. Pre-test and post-test evaluations were used to gather data, and the N-gain computation was used to analyze the results in order to gauge learning improvement. With an N-gain of 0.49, which indicates moderate effectiveness, the data demonstrate a considerable rise in post-test scores relative to pre-test levels. PBL has been shown to improve student participation in the learning process as well as academic knowledge.